Growing up in a larger body: youth- and parent-reported triggers for illness and barriers to recovery from anorexia nervosa - Grace B. Jhe; Michelle Recto; Julia A. Vitagliano; Kelsey L. Rose; Tracy Richmond; Melissa Freizinger; Jessica Lin (Journal of Eating Disorders)
Abstract Background A significant portion of youth with anorexia nervosa (AN) or atypical anorexia nervosa (AAN) have history of ‘overweight/obesity’ (i.e., body mass index ≥ 85th percentile for age-and-sex) prior to the onset of the eating disorder (ED) diagnosis, but research on this population remains limited. The present study used semi-structured interviews to explore themes related to triggers of weight loss, treatment, and recovery among youth with AN/AAN and history of ‘overweight/obesity,’ and their parents. Method The sample included eleven youth and parent dyads (Median [IQR] age of youth = 16.0 (1.5) years, 90.9% female, 90.9% White, 27.3% Hispanic) who were evaluated for an ED in a multidisciplinary ED program at a pediatric hospital between November 2020 and April 2021. Nine youth and separately, nine parents of these 11 dyads completed semi-structured interviews with the research team. Seven matched pairs of patients and parents completed demographic surveys and study interviews. Interviews were recorded, transcribed, and coded by four research team members using a reflexive thematic approach. Results Weight stigma was the most frequently reported theme for a trigger for weight loss that led to the onset for developing AN/AAN by both youth and parents. Regarding barriers to recovery, themes from more than a half of youth included uncertainty of weight goals in treatment and feeling they are “not sick enough.” Notable themes for attitudes towards treatment from most parents included general agreement with clinician recommendations, but also an uncertainty of weight restoration goals and a belief that their child need to have a “normal” weight. Conclusion These results highlighted how the majority of interviewed youth with history of ‘overweight/obesity’ reported weight stigma as both a trigger for the development of AN/AAN as well as a barrier to recovering. Internalized weight stigma among parents may influence their attitudes towards weight restoration as a treatment goal where these youth and parents may experience uncertainty of weight goals in treatment. This study demonstrated triggers and barriers to treatment that may be unique to youth with ED and history of ‘overweight/obesity’ and more research is needed to address weight stigma in multidisciplinary ED treatment for this understudied population.